1996
DOI: 10.1021/ja961601m
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Pr@C82 and Pr2@C80

Abstract: Pr@C82 and Pr2@C80 have been isolated with a purity of >99.0% by an efficient solvent extraction procedure, followed by HPLC separation. UV−VIS−NIR spectra of the metallofullerenes were measured in the wavelength range from 300 to 2100 nm. The X-ray photoelectron spectra of Pr@C82 and Pr2@C80 suggest that the Pr atoms inside the carbon cages all exist in a cationic form represented by Pr3+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
66
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 32 publications
2
66
1
Order By: Relevance
“…5͒ and for Pr@ C 82 . 6 Our calculation as shown in Fig. 4͑f͒ for 3d XPS of Pr@ C 82 also consists of 4f 2 and 4f 3 v គ and agrees well with the experiment.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…5͒ and for Pr@ C 82 . 6 Our calculation as shown in Fig. 4͑f͒ for 3d XPS of Pr@ C 82 also consists of 4f 2 and 4f 3 v គ and agrees well with the experiment.…”
supporting
confidence: 86%
“…2 It is known that the charge transfer between metal and fullerene cage strongly relates to the physical properties such as superconductivity. 3 The charge transfer effect and the valence of the metal ion have been studied by several methods: electron-spin resonance, 4 x-ray photoelectron spectroscopy ͑XPS͒, 5,6 ultraviolet photoelectron spectroscopy ͑UV-PES͒, [7][8][9] x-ray absorption spectroscopy ͑XAS͒, 10 and Raman spectroscopy. 11 In XAS ͑Ref.…”
mentioning
confidence: 99%
“…Most of the monometallofullerenes prepared so far have been based on C 82 and group III metals (M) Sc, Y, La) and the majority of the lanthanide elements. [4][5][6] Due to difficulties in producing pure samples in large quantities, further experimental characterization of endohedral metallofullerenes has been hindered. To improve the production efficiency of metallofullerene, it is imperative to understand the mechanism of metallofullerene formation in the arc-discharge.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Many experimental results have shown that a group-III metal ͑M ϭSo, Y, La͒ or lanthanide atom could be attached to a fullerene C 82 molecule. 1-8 X-ray absorption fine-structure ͑EXAFS͒ studies on Y@C 82 have provided strong evidence that the metal atom is located inside the fullerene cage.…”
Section: Introductionmentioning
confidence: 99%